2019
DOI: 10.1002/hbm.24553
|View full text |Cite
|
Sign up to set email alerts
|

Children show hemispheric differences in the basic auditory response properties

Abstract: Auditory cortex in each hemisphere shows preference to sounds from the opposite hemifield in the auditory space. Besides this contralateral dominance, the auditory cortex shows functional and structural lateralization, presumably influencing the features of subsequent auditory processing. Children have been shown to differ from adults in the hemispheric balance of activation in higher‐order auditory based tasks. We studied, first, whether the contralateral dominance can be detected in 7‐ to 8‐year‐old children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 56 publications
(118 reference statements)
5
54
0
Order By: Relevance
“…This protracted development of the left hemisphere arguably provides a time window where the brain can flexibly employ its resources which should be useful in the everchanging environment of the child brain. Indeed, others have argued for stronger experience-driven plasticity in the left-hemisphere (Renvall et al, 2012; Parviainen et al, 2019). However, handedness has also been shown to affect hemispheric dominance of neuromagnetic responses to sounds (Kirveskari et al, 2006) and as such our reported effect might depend on handedness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This protracted development of the left hemisphere arguably provides a time window where the brain can flexibly employ its resources which should be useful in the everchanging environment of the child brain. Indeed, others have argued for stronger experience-driven plasticity in the left-hemisphere (Renvall et al, 2012; Parviainen et al, 2019). However, handedness has also been shown to affect hemispheric dominance of neuromagnetic responses to sounds (Kirveskari et al, 2006) and as such our reported effect might depend on handedness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, children show an auditory evoked response (i.e. N250m) that is reported even by passive stimulation, using different sound types, and under different attentional conditions (van Bijnen et al, 2019; Parviainen et al, 2019; Albrecht et al, 2000; Takeshita et al, 2002; Johnstone et al, 1996). This response is typically absent in adults.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations